Concept Seminar: “Political Education – Before and After the Referendum” (Concept: The Journal of Contemporary Community Education Practice Theory, 2014)
Attended by around 50 people, a mixture of council Community Learning & Development workers, voluntary groups, students and academics, this event featured four main presentations about work in the field of political education for different age groups and communities. The referendum was considered from the point of view of “the problems it raises in terms of curriculum and teaching as well as some of the new and unique opportunities it opens up for political education”.